Risk of Autism Spectrum Disorder (ASD) Among 18 to 48 Month Old Children: A Multi-Center Study in Qatar - Aisha Abdulraheem Sameea MBBS; Ekram Wassim Abd El-Wahab PhD; Sherif Omar Osman DrPH (SAGE Publishing, 2024)
Background. Little is known about autism spectrum disorder (ASD) in Qatar. The lack of consensus in ASD screening has led to differences in the reported prevalence with escalating rates over time. Objective(s). To screen for ASD and to identify associate factors among Qatary children aged 18 to 48 months. Methods. A cross-sectional study included 600 eligible children at 10 Primary Health Care Centers (PHCCs) in Qatar. Identification of ASD was based on the M-CHAT™ criteria. Results. The number of ASD screen-positive children in the M-CHAT™ was 25.13 per 10.000, and was significantly associated with older maternal age (10.5%) and history of neonatal hyperbilirubinemia (20.0%) [AOR] = 4.88; 95%[CI]: 1.50-16.30)]. The Odds of detecting ASD was lower in children below 2 years of age (AOR = 0.92; 95% CI: 0.87-0.98]). Conclusion. This study demonstrates the utility of M-CHAT™ for ASD screening in PHCCs. Identification of the factors associated with positive ASD screening can highlight areas suitable for future intervention.